The university as executor of the goals of the state and its impact on the business world as a foundation for the promotion of the nation's economy. With a focus on gender equity - Loaiza Massuh, Eva María de Lourdes; Salinas Falquez, Silvia; Salazar Torres, Patricia; Solis Marin, Betzabe (Revista Universidad de Guayaquil, 2024)
The current economic scenario and its obvious results directly and unavoidably affect financial growth, causing serious social, cultural and political collateral consequences. The research based on documents, notably bibliographic, was the one used for the writing of this article that aims to demonstrate the indispensable and objective interaction between the University, the State and the Company, as an essential motor of the economic development of the Country, with a focus towards gender equity. The Institutions of Higher Education, (IES) intervene as an entity of generation and transfer of knowledge, developing scientific research and additionally scrutinizing the industry, so that it is where the results of these discoveries are executed, technically promoting the innovation in existing services, goods, and merchandise, as well as the creation of new products. On the other hand, it is the responsibility of HEIs to promote inclusive education, in addition to the concretion of the Declaration of Human Rights, where it is considered that equity between women and men has been aggravated by the current socio-economic crisis, which makes the principle equality remains paramount (Campoy-Carbajales, 2017). The State intervenes as an investor entity that directs the resources with the objective of obtaining a social and cultural profitability, strengthening its government policy and the competitiveness indexes. The final axis in this trilogy is the Company, as the beneficiary of these products, because it will be able to have up-to-date and accurate information to implement it, either in the safeguarding technology of production or in the creation of new business plans, as a result of this integration, optimum results will be obtained, such as the strengthened fomentation of entrepreneurship.
Keywords: university; state; enterprise; equity; inclusive education; investor; production